Intra and Interobserver Variability in the B-mode Transorbital Sonographic Measurement of the Optic Nerve Sheath Diameter in Healthy Nepalese Individuals - Ghimire, Prasanna; Chand, Birendra Bahadur; Mahat, Yug Bijay; Ojha, Subash; Singh, Bhuwaneshwar Prasad (Nepalese Journal of Radiology, 2019)
Introduction: Ocular ultrasound has gained importance as a non-invasive imaging technique in the screening, diagnosis and treatment management of intracranial hypertension. The aim of our study was to estimate the intra and interobserver variability on B-mode ocular ultrasound measurement of optic nerve sheath diameter (ONSD). Methods: ONSD of the right eye was measured by ultrasound examination among 120 healthy adult volunteers. The ONSD was assessed 3 mm behind the globe and two serial measurements were taken by two observers who were blinded to each other’s findings. Results: Age of the volunteers ranged from 18 to 27 years with a mean age of 23.07 +/- SD of 2.486. The mean of ONSDs of two observers was 4.168 +/- SD of 0.54 mm. The intraclass correlation coefficient for first and second observers was 0.997 and 0.978 respectively at 95% confidence interval. The interobserver intraclass correlation coefficient was 0.977 at 95% confidence interval. No correlation of age and gender was noted with ONSD. Conclusions: B-mode transorbital ultrasound measurement of ONSD is highly reproducible with significant intra-observer and inter-observer agreement. Ultrasound measurement of ONSD measurements can serve as indispensable tool in critical care.